Psychometric Properties of the Persian Version of the Exercise Self-Efficacy Scale in Pregnant Women - Maryam Alborzi; Seyedeh Zahra Masoumi; Farzaneh Soltani; Farideh Kazemi; Leili Tapak (Hamadan University of Medical Sciences, 2021)
Background and Objective: Proper and adequate physical activity during pregnancy significantly impacts maternal health and fetal development. Unfortunately, no tools are available to measure the self-efficacy of sports activity in Iranian pregnant women. Material and Methods: After translating the questionnaire by the forward-backward method, the quantitative and qualitative face validity and the qualitative and quantitative content validity were assessed. An exploratory factor analysis approach was used to determine the validity of the structure. Simultaneous validity of the instrument was also evaluated using the Scherer General Self-Efficacy Questionnaire. Cronbach's alpha was used to assess the internal stability of the sports self-efficacy questionnaire, and the ICC was used to assess the reproducibility. Results: Content validity was performed qualitatively and the corrections mentioned by the professors were applied, and none of the options were removed in quantitative content validity. In order to determine the construct validity of the questionnaire, exploratory factor analysis was performed, and the KMO test value was 0.765. Thus, 37.5% of the variance was explained by the first factor and 14% by the second factor. The Scherer general self-efficacy correlation coefficient for pregnant women was 0.446 with P-value <0.001. Cronbach's alpha was 0.76 for both domains and 0.81 for the whole scale. ICC was also calculated to be 0.99 for the questionnaire areas and the entire tool. Conclusion:  The Persian version of the questionnaire to assess exercise self-efficacy during pregnancy has good validity and reliability and can measure exercise self-efficacy during pregnancy.